2019
DOI: 10.1080/02670844.2018.1541298
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of light-resistant printing UV ink modified with nano-TiO2 on wood substrate

Abstract: Nano-TiO 2 was used to modify the yellow UV ink by physically blending. The modified and unmodified UV ink was respectively used for wood printing. The aging test was carried out on the printed wood and several physical, morphological, and chemical analyses were performed. The results showed that the UV ink underwent oxidation during aging, caused colour and gloss changes, surface bubbling, and polymer chain decomposition both for the unmodified and nano-TiO 2 groups. However, on a macro level, the main struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In theory, the dry film thickness was 18 µm. The film sample was then dried in a cool, dry, and dark environment for 1 week before use [23]. Three replicates were coated for each sample.…”
Section: Coatingmentioning
confidence: 99%
“…In theory, the dry film thickness was 18 µm. The film sample was then dried in a cool, dry, and dark environment for 1 week before use [23]. Three replicates were coated for each sample.…”
Section: Coatingmentioning
confidence: 99%
“…The characterizations of the samples were carried out by scanning electron microscope coupled with energy dispersed X-ray analysis, atomic force microscopy (AFM), Fourier transform infrared spectroscopy equipped with an attenuated total reflection (ATR-FTIR), and X-ray photoelectron spectra (XPS) analyses [21]. The microstructures of the above samples were observed by scanning electron microscope (JEOL JSM-6301F, Japan) with an acceleration voltage of 20 kV.…”
Section: Characterizations and Testsmentioning
confidence: 99%
“…The heat-treated wood is exposed to ultraviolet radiation, rain, microorganism, termites, and attack by drilling animals for outdoor occasions [4][5][6], while inorganic-wood composites give new functions to wood. Synergies between wood and inorganic components enhance the thermal stability, color fastness, mechanical performance, and dimensional stability of the wood [7][8][9]. Previous studies have shown that hybrid inorganic-organic film can effectively reduce the moisture absorption of the wood [10].…”
Section: Introductionmentioning
confidence: 99%